The 'Bandung spirit' and solidarist internationalism. Issue 4 (3rd July 2016) - Weber, Heloise; Winanti, Poppy
ABSTRACT: It must come as no surprise that traces of any continuing relevance of the 'Bandung spirit' are enthusiastically being sought in the wake of the sixtieth anniversary of the Asian-African Conference. It was the first high-profile formal conference of newly independent (or 'about-to-be independent') post-colonial states at a rather momentous historical conjuncture: the continuing struggles for decolonisation were pronounced in the context of the Cold War. The Final Communiqué of the Bandung conference strongly articulated a collective political project against colonialism and imperialism, and for self-determination and racial equality, while already laying the foundations for the idea of strategic non-alignment in the context of the Cold War. It is in this sense that the Bandung conference has come to be emblematic of an event that inaugurated a radically different international political landscape to the immediate post-1945 world order. In this article, the authors focus specifically on the development aspirations articulated at the Asian-African Conference in Bandung, which they argue are the site of struggles and contradictions. As the authors show, the 'Bandung spirit' underlined the political project of Third Worldism, as well as the call for a new international economic order in the 1970s. Yet, they also identify some constraints and contradictions that the 'Bandung spirit' had to navigate and the challenges it was up against. In the final part of the article, the authors briefly discuss the extent to which the 'Bandung spirit' continues to resonate in contemporary global politics of development.